Building Resilience : Integrating Climate and Disaster Risk into Development - World Bank (Washington, DC, 2014)
This report presents the World Bank Group's experience in climate and disaster resilient development and contends that it is essential to eliminate extreme poverty and achieve shared prosperity by 2030. The report argues for closer collaboration between the climate resilience and disaster risk management communities through the incorporation of climate and disaster resilience into broader development processes. Selected case studies are used to illustrate promising approaches, lessons learned, and remaining challenges all in contribution to the loss and damage discussions under the United Nations Framework Convention on Climate Change (UNFCCC). The introduction provides an overview of the UNFCCC and also introduces key concepts and definitions relevant to climate and disaster resilient development. Section two describes the impacts of globally increasing weather-related disasters in recent decades. Section three summarizes how the World Bank Group's goals to end extreme poverty and boost shared prosperity are expected to be affected by rising disaster losses in a changing climate. Section four discusses the issue of attribution in weather-related disasters, and the additional start-up costs involved in climate and disaster resilient development. Section five builds upon the processes and instruments developed by the climate resilience and the disaster risk management communities of practice to provide some early lessons learned in this increasingly merging field. Section six highlights case studies and emerging good practices in climate and disaster resilient development. Section seven concludes the report, summarizing key lessons learned and identifying potential gaps and avenues for future work.